Hox functional diversity: Novel insights from flexible motif folding and plastic protein interaction. (16th January 2017) - Ortiz‐Lombardia, Miguel; Foos, Nicolas; Maurel‐Zaffran, Corinne; Saurin, Andrew J.; Graba, Yacine
Abstract : How the formidable diversity of forms emerges from developmental and evolutionary processes is one of the most fascinating questions in biology. The homeodomain‐containing Hox proteins were recognized early on as major actors in diversifying animal body plans. The molecular mechanisms underlying how this transcription factor family controls a large array of context‐ and cell‐specific biological functions is, however, still poorly understood. Clues to functional diversity have emerged from studies exploring how Hox protein activity is controlled through interactions with PBC class proteins, also evolutionary conserved HD‐containing proteins. Recent structural data and molecular dynamic simulations add further mechanistic insights into Hox protein mode of action, suggesting that flexible folding of protein motifs allows for plastic protein interaction. As we discuss in this review, these findings define a novel type of Hox‐PBC interaction, weak and dynamic instead of strong and static, hence providing novel clues to understanding Hox transcriptional specificity and diversity. Abstract : The characterization of Ubx‐Exd‐DNA complexes identifies a novel type of Hox‐PBC interaction mode. The interaction is paralog specific, plastic, and relies on flexible folding of sequences C‐terminal (side chains displayed) to the Ubx homeodomain (emphasized by the green, yellow, and magenta coloring of the Ubx protein).